The Ligand‐Based Quintuple Bond‐Shortening Concept and Some of Its Limitations. Issue 30 (2nd July 2013) - Noor, Awal; Bauer, Tobias; Todorova, Tanya K.; Weber, Birgit; Gagliardi, Laura; Kempe, Rhett
Abstract Herein, the ligand‐based concept of shortening quintuple bonds and some of its limitations are reported. In dichromium–diguanidinato complexes, the length of the quintuple bond can be influenced by the substituent at the central carbon atom of the used ligand. The guanidinato ligand with a 2, 6‐dimethylpiperidine backbone was found to be the optimal ligand. The reduction of its chromium(II) chloride–ate complex gave a quintuply bonded bimetallic complex with a CrCr distance of 1.7056 (12) Å. Its metal–metal distance, the shortest observed in any stable compound yet, is of essentially the same length as that of the longest alkane CC bond (1.704 (4) Å). Both molecules, the alkane and the Cr complex, are of remarkable stability. Furthermore, an unsupported CrI dimer with an effective bond order (EBO) of 1.25 between the two metal atoms, indicated by CASSCF/CASPT2 calculations, was isolated as a by‐product. The formation of this by‐product indicates that with a certain bulk of the guanidinato ligand, other coordination isomers become relevant. Over‐reduction takes place, and a chromium–arene sandwich complex structurally related to the classic dibenzene chromium complex was observed, even when bulkier substituents are introduced at the central carbon atom of the used guanidinato ligand.